2020
DOI: 10.1037/lhb0000423
|View full text |Cite
|
Sign up to set email alerts
|

Mock jurors’ evaluation of firearm examiner testimony.

Abstract: Objectives: Firearms experts traditionally have testified that a weapon leaves "unique" toolmarks, so bullets or cartridge casings can be visually examined and conclusively matched to a particular firearm. Recently, due to scientific critiques, Department of Justice policy, and judges' rulings, firearms experts have tempered their conclusions. In two experiments, we tested whether this ostensibly more cautious language has its intended effect on jurors (Experiment 1), and whether cross-examination impacts juro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Cross-examination presents a potential safeguard against unreliable forensic testimony (see Edmond et al, 2014), but research has yielded mixed findings as to its efficacy. Some have found that crossexamination had little or no effect on a forensic expert's credibility (Garrett et al, 2020;Koehler, 2011), which others found that some strategies were more (e.g., emphasizing the subjectivity of the expert's opinion; Thompson & Scurich, 2019) or less (e.g., attacking the expert's credentials; Lieberman et al, 2008) effective than others. Future work should continue to examine which cross-examination strategies enable jurors to rightly discount dubious forensic testimony without creating a blanket skepticism that undercuts even valid forensic evidence.…”
Section: Jurors' U Nderstandingmentioning
confidence: 99%
“…Cross-examination presents a potential safeguard against unreliable forensic testimony (see Edmond et al, 2014), but research has yielded mixed findings as to its efficacy. Some have found that crossexamination had little or no effect on a forensic expert's credibility (Garrett et al, 2020;Koehler, 2011), which others found that some strategies were more (e.g., emphasizing the subjectivity of the expert's opinion; Thompson & Scurich, 2019) or less (e.g., attacking the expert's credentials; Lieberman et al, 2008) effective than others. Future work should continue to examine which cross-examination strategies enable jurors to rightly discount dubious forensic testimony without creating a blanket skepticism that undercuts even valid forensic evidence.…”
Section: Jurors' U Nderstandingmentioning
confidence: 99%
“…This research has occurred largely in the context of mock juror studies. These studies, focusing on feature comparison practices like firearms [62], bitemark [32,63], and fingerprint analysis [18,32,64,65], tend to find only a modest relationship between the stated limitations of the evidence and mock jurors' assessment of that evidence (and the associated expert). Mock jurors will, for example, take into account a forensic examiner's proficiency when assessing their evidence and expertise [32,64].…”
Section: Part III the Credibility Of Sciencementioning
confidence: 99%
“…Converging with these findings, other work finds only a weak relationship between expressions of uncertainty in an expert's opinion and the weight mock jurors accord those opinions:[18,62,65]. On the importance of careful reporting generally, see[66].…”
mentioning
confidence: 93%
“…The PCAST report concluded that the method was not sufficiently validated on the basis of this single study. In response to these types of concerns, judicial rulings, and new U.S. Department of Justice Guidelines, firearm examiners in some jurisdictions have tempered the description of their conclusions in criminal court testimony [ [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%